Corrupt bureaucrats, bad managers, and the slow race between education and technology - Ivan Lyubimov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​We study a developing economy in which the representative firm's production function exhibits complementarities between human capital and the available level of technology. The firm invests in the acquisition of new technology, while employees decide how much human capital to acquire. The rate of human capital accumulation positively affects the economy's growth rate, and therefore in our baseline case a reform that improves the educational system boosts growth. An important caveat, however, is that the absence of robust institutions may lead to lax enforcement of property rights and limit the incentives for firms to invest in new technology. The lack of investment in technology constrains demand for human capital and undermines the success of the education reform. It can even lead to a brain drain as individuals take advantage of the education reform and then move to an economy with higher demand for their acquired skills. We also consider our model findings with respect to the real-world case of Russia. Our main conclusion is that measures to improve the school system need to be accompanied by other institution-building measures that enhance property rights, promote good management practices and reduce incentives to engage in corrupt behaviors.
URN:NBN:fi:bof-201609301436
Keywords: O43; P16; 330